Ester Prodrugs of Ketoprofen: Synthesis, In Vitro Stability, In Vivo Biological Evaluation and In Silico Comparative Docking Studies Against COX-1 and COX-2 - Ahmed, Musa; Azam, Faizul; Gbaj, Abdul; E. Zetrini, Abdulmottaleb; S. Abodlal, Amna; Rghigh, Abir; Elmahdi, Eman; Hamza, Amel; Salama, Mabruk; M. Bensaber, Salah (Current Drug Discovery Technologies, 2016)
Prompted by the ineptness of the currently used non-steroidal antiinflammatory drugs (NSAIDs) to control gastric mucosal and renal adverse reactions, several ester prodrugs of ketoprofen were synthesized and characterized by IR, 1H NMR and mass spectral data. Physicochemical properties such as aqueous solubility, octanol-water partition coefficient log P, chemical stability and enzymatic hydrolysis of the synthesized molecules have been studied to assess their potential as prodrugs. The obtained results confirmed that all ester prodrugs are chemically stable, possess increased lipophilicity compared to their parent compounds and converted to the active drugs in vivo. All of the tested ester prodrugs exhibited marked anti-inflammatory activity ranging from 91.8% to 113.3% in comparison with the parent drug, ketoprofen. A mutual prodrug obtained from two antiinflammatory molecules, ketoprofen and salicylic acid has been noted to potentiate the activity making it most active molecule of the series. The ulcerogenic index of the ester prodrugs was significantly lower than the parent drug, ketoprofen. Comparative docking studies against X-ray crystal structures of COX-1 and COX-2 further provided understanding of their interaction with the cyclooxygenases that will facilitate design of better inhibitors (or prodrugs) with sufficient specificity for COX-2 against COX-1. The study offers an innovative strategy for finding a molecule with safer therapeutic profile for longterm treatment of inflammatory diseases.
Keywords: COX-1